An Unpublished Stela of Nedjesankh/Iew and His Family (CG 20394/JE 15107) - Joseph, Amgad.
This article is the publication of a stela from Abydos that will be exhibited in the Grand Egyptian Museum, Giza (CG 20394/JE 15108). The stela can be dated to early in the first part of the Thirteenth Dynasty, probably in the reign of King Ameny-Qemau, on the grounds of its stylistic, phraseological, iconographic, and epigraphic details. It is the only monument that records the names of Queen Nofret, who may have been the wife of Ameny-Qemau and their daughter Princess Hatshepsut. It documents the marriage between Hatshepsut and the stela’s owner, the 'tw n tt ha', Commander of the [Ruler’s] Crew, Nedjesankh/Iew. It also depicts their children, and the children of another woman called Nebuemwakh who may have been a secondary wife of Nedjesankh/Iew. The author describes the stela, deals with its individual idiosyncrasies, texts, and focuses on the genealogy of its individuals. http://dx.doi.org/10.5913/jarce.55.2019.a005